Annual reports in computational chemistry. - Dixon, David A. (Annual Reports in Computational Chemistry, 2017)
Annual Reports in Computational Chemistry, Volume 14, provides timely and critical reviews of important topics in computational chemistry. Topics covered in this series include quantum chemistry, molecular mechanics, force fields, chemical education, and applications in academic and industrial settings. Focusing on the most recent literature and advances in the field, each article covers a specific topic of importance to computational chemists.